Efeito da composição elementar atribuída à poluição antrópica na qualidade das águas e sedimento do Rio Marrecas (PR, Brasil) como destacada por análises estatísticas multivariadas - Hellmann, Liliane (2020)
The monitoring of physical-chemical parameters such as the concentration of metals in sediment and surface water used for human supply is essential due to their potential toxic and bio cumulative effects. In this sense, this research sought to analyze the physical-chemical parameters and trace elements in the water and sediment, as well as to identify potential sources of contamination, using multivariate statistics on the Marrecas River, located in the city of Francisco Beltrão, PR, Brazil. The technique of X-ray fluorescence by total reflection (TXRF) was used to identify the trace elements and to quantify their concentrations in nine different sampling points distributed from the source to the mouth of the river, over a monitoring period of 12 months. Fifteen chemical elements were identified and quantified in the water and sediment samples. Through the multivariate statistical analysis, the most significant parameters and possible polluting sources were defined. Principal component analysis (PCA), the correlation between parameters by Spearman's correlation, and the similarity between the sampling points were used in the study using cluster analysis (Cluster). Water contamination was further evaluated using the heavy metal pollution index (HPI) and heavy metal assessment index (HEI). The results showed that the physical-chemical parameters of pH and BOD5 are not in compliance with the maximum permissible limits stipulated by Brazilian legislation. Based on the PCA and Spearman's correlation, there is strong evidence of contamination in water as well as in sediment, formed naturally by the elements of Ti, V, Mn, Fe, and of an anthropogenic origin, with a spatial tendency composed by the elements Ca, Ni, Cu, and Zn. The HPI, HEI, and the spatial distribution patterns of the pollution sources show poor water quality. These results highlight serious indication of contamination by both natural and anthropogenic causes and show a necessary concern in relation to the health of the population directly affected, as well as the need to implement public policies and actions to raise public awareness to improve quality and to strengthen the environmental preservation of this fundamental water resource.